Le carte cantano. La musica nel Fondo Adelaide Ristori al Museo Biblioteca dell’Attore di Genova - Raffaele Mellace (Drammaturgia)
This essay aims at proposing a map of the relationship between Adelaid Ristori and music, as it emerges from consulting the Adelaide Ristori Archive at the Museo Biblioteca dell’Attore in Genoa. The analysis of the documents connected with music reveals the multiplicity of the presence of music in the actress’s professional activity, as well as, probably, her private life. It is possible to detect such a presence in a few practices which intertwin without completely overlapping, such as those witnessed by stage music owned by Ristori or dedicated to her. Such an overview implies a thick web of relationships with representatives of the musical world, of the show business and contemporary aristocracy. The valuable documentation inquired in the essay, just recently listed, has never been evaluated in its entirety. This essay aims to organize a preliminary map which will hopefully boost further studies.